Electronic Circular Dichroism Imaging (ECDi) Casts a New Light on the Origin of Solid‐State Chiroptical Properties. Issue 4 (21st December 2021) - Górecki, Marcin; Lipparini, Filippo; Albano, Gianluigi; Jávorfi, Tamás; Hussain, Rohanah; Siligardi, Giuliano; Pescitelli, Gennaro; Di Bari, Lorenzo
Abstract: Solid‐state ECD (ss‐ECD) spectra of a model microcrystalline solid, finasteride, dispersed into a KCl pellet were recorded by using the synchrotron radiation source at the Diamond B23 beamline. Scanning a surface of 36 mm 2 with a step of 0.5 mm, we measured a set of ECD imaging (ECD i ) spectra very different from each other and from the ss‐ECD recorded with a bench‐top instrument (1 cm 2 area). This is due to the anisotropic part of the ECD (ACD), which averages to zero in solution or on a large number of randomly oriented crystallites, but can otherwise be extremely large. Two‐way singular value decomposition (SVD) analysis, through experimental and simulated TDDFT spectra, disclosed that the measured and theoretical principal components are in line with each other. This finding demonstrates that the observed isotropic ss‐ECD spectrum is governed by the anisotropy of locally oriented crystals. It also introduces a new quality for ss‐ECD measurements and opens a new future for probing and mapping chiral materials in the solid state such as active pharmaceutical ingredients (APIs). Abstract : It depends how you look at it : By exploring randomly formed domains of microcrystalline finasteride dispersed in a KCl pellet with the spatial resolution of 0.1 mm granted by synchrotron source, we noticed that anisotropic ECD i (ACD) spectra might be very different from the emergent solid‐state ECD spectrum recorded on a commercial instrument, which is similar to the solution ECD. Consequently, we got an exclusive insight into the critical role played by local domains.